1980
DOI: 10.1126/science.6771872
|View full text |Cite
|
Sign up to set email alerts
|

Effective Pulmonary Ventilation with Small-Volume Oscillations At High Frequency

Abstract: At high oscillation frequencies (4 to 30 hertz), effective alveolar ventilation can be achieved with tidal volumes much smaller than the anatomic dead space. An explanation of this phenomenon is given in terms of the combined effects of diffusion and convection and in terms of data consistent with the hypothesis. Theory and experimental results both show that the significant variable determining the effectiveness of gas exchange is the amplitude of the oscillatory flow rate independent of the individual values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
47
1
1

Year Published

1981
1981
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(52 citation statements)
references
References 7 publications
3
47
1
1
Order By: Relevance
“…8) to regional gas exchange during HFV is unclear. An early theoretical study (34) predicted and later experimental studies (35)(36)(37)(38) confirmed that overall gas exchange during HFV would depend upon the product of f and VT, rather than each individually, in the limit when VT'S were infinitesimally small compared with dead space, and that there would be an independent influence of VT upon gas exchange when VT's approached appreciable fractions of the dead space, i.e., when bulk convection would become significant relative to gas mixing phenomena. It has also been speculated that the independent VT effect might be due to direct ventilation 'of nearby alveoli in the asymmetrical airway tree (39), due to complexities in characterizing the gas concentration boundary conditions at the airway opening and at the alveolus (36,40), due to streaming flows (41), and due to the physics of compartmental mixing (42).…”
Section: Resultsmentioning
confidence: 99%
“…8) to regional gas exchange during HFV is unclear. An early theoretical study (34) predicted and later experimental studies (35)(36)(37)(38) confirmed that overall gas exchange during HFV would depend upon the product of f and VT, rather than each individually, in the limit when VT'S were infinitesimally small compared with dead space, and that there would be an independent influence of VT upon gas exchange when VT's approached appreciable fractions of the dead space, i.e., when bulk convection would become significant relative to gas mixing phenomena. It has also been speculated that the independent VT effect might be due to direct ventilation 'of nearby alveoli in the asymmetrical airway tree (39), due to complexities in characterizing the gas concentration boundary conditions at the airway opening and at the alveolus (36,40), due to streaming flows (41), and due to the physics of compartmental mixing (42).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, however, this traditional concept has been challenged by experimental observations demonstrat-ing that effective alveolar ventilation can occur with VT considerably less than dead-space volume provided that the ventilatory frequencies are sufficiently large (1)(2)(3)(4)(5). Although this has by now been well established by a number of studies, the physical mechanisms that account for the observed gas exchange are not known with certainty.…”
mentioning
confidence: 91%
“…To confirm that during an experimental run of HFV the oscillations did not introduce an artifact, we measured the integral of the CO2 concentration from the bias flow using a constant CO2 source in place of the dog while oscillatory frequency and stroke volume were varied and found this integral to be constant. In dogs 3-6, whose data were presented in part in our previous paper (5), and in dogs 8 and 9, we corrected the integral of CO2 concentration for a small systematic error (7 ml/min) in our CO2 analyzer calibration. This problem was eliminated for the experiments in dogs 10-16. We found that changes in the fractional alveolar CO2 concentration (FACO2) resulted in a change in VCo2 at any Vosc.…”
mentioning
confidence: 99%
“…These results suggest that using the high frequency ventilator tested, to minimize alveolar barotrauma one should choose the highest frequency where gas exchange is adequate. (Pediatr Res 19: 162-166,1985) Abbreviations HFV, high frequency-low tidal volume ventilation HFV is currently under investigation as a new technique for treatment of adults and infants with respiratory failure (2,3,6,8,10,15). Its major advantage is the potential for adequate gas exchange with lower dynamic pressures within the airways.…”
mentioning
confidence: 99%